Assessing gender disparities in farmers’ access and use of climate-smart agriculture in Southern Tanzania - Nchanji, Eileen Bogweh; Ndunguru, Agness; Kabungo, Catherine; Katunzi, Adolph; Nyamolo, Victor; Ouya, Fredrick Ochieng'; Mutua, Mercy; Waswa, Boaz; Cosmas Kweyu Lutomia (Springer, 2025)
The importance of common bean in Tanzania is increasingly challenged by climate change, which increases women's vulnerability and undermines the contribution of the crop to food security and rural livelihoods. This study assessed gender differences in the use of climate-smart agriculture technologies and practices among bean farmers in Tanzania. A multi-stage sampling procedure was used to collect data from 364 smallholder bean farmers. Descriptive statistics and a multivariate probit model were employed to analyse the determinants of farmers' adoption of climate-smart agricultural technologies and practices in common bean production. Results revealed that men dominated climate-adaptation decision-making processes at the household level because of their ownership and control over access to land, and access to agricultural support services. Older men farmers demonstrated a positive and significantly higher likelihood of adopting improved seeds (β = 0.026; p < 0.01), signifying they possess greater accumulated knowledge and wealth compared to women farmers and youths. Women farmers also had lower levels of education with fewer technological access contributing to their low uptake of climate-smart technologies, aggravating their vulnerability to climate change. Enhancing inclusive gender access to land and group-based approaches to information dissemination, and capacity building, would be relevant in enabling men, women, and young farmers to improve their adaptive and resilience capacities to climate change. Gender dynamics should be considered in designing climate-smart agriculture policies and implementation of climate-smart agriculture programs and policies to improve farmers' resilience to climate change.